Increased sIL-2Rα leads to obstruction of IL-2 biological function and Treg cells differentiation in SLE patients via binding to IL-2 - Long, Dan; Yu, Shujiao; Zhang, Lu; Guo, Yang; Xu, Shumin; Rao, Yuting; Huang, Zikun; Luo, Qing; Li, Junming (Frontiers in Immunology, 2022)
Background: The decrease of IL-2 level is believed to play an important role in the disease occurrence and development of SLE, but the relevant mechanisms have not been fully clarified. Many studies have found that the level of soluble interleukin 2 receptor (sIL-2R) in SLE patients is significantly increased. Considering the fact that sIL-2R has the ability to bind IL-2, we want to know whether the increased sIL-2R has some impact on the level and function of IL-2 in SLE patients. Methods: New onset SLE patients, treated SLE patients and healthy volunteers were recruited. The levels of serum IL-2, IL-2 mRNA in PBMCs and serum sIL-2R were detected and compared in these subjects. Two mixed solid-phase sandwich ELISA system were designed to detected the exist of sIL-2R-IL-2 complex. The sera from SLE patients were pretreated with or without immune complex dissociation solution and detected for IL-2 levels. The IL-2 levels of IL-2 standards and sera from HCs were detected before and after co-incubation with or without recombinant sIL-2R or serum samples with high sIL-2R level. CTLL-2 cell proliferation test was used to measure the bioactivity of IL-2. The frequencies of Treg cells were detected by flow cytometry before and after the addition of recombinant sIL-2R. Results: The levels of serum IL-2 in SLE patients were significantly decreased and negatively correlated with SLEDAI. However, there was no significant difference in IL-2 mRNA levels in PBMCs between SLE patients and healthy controls. The levels of serum sIL-2R in SLE patients were significantly increased, positively correlated with the SLEDAI and negatively correlated with the levels of serum IL-2. sIL-2R was shown to bind to IL-2 to form immune complex, resulting in false reduction in the detection level of serum IL-2 and significant decrease in biological activity of IL-2. And, the increase of sIL-2R was demonstrated to be one of the important mechanisms for the obstruction of Treg cells differentiation in SLE patients. Conclusion: Increased serum sIL-2R can bind to IL-2, leading to obstruction of IL-2 activity and Treg cells differentiation.